(untitled) (Annals of Medical Research, 2021)
Aim: Ankylosing spondylitis (AS) is a systemic chronic inflammatory disease that has various adverse effects on cardiac autonomic functions. On the other hand, there is no data regarding the effects of cardiac rehabilitation on cardiac autonomic functions in AS patients. In this study, we aimed to investigate the effects of cardiac rehabilitation on cardiac autonomic nervous system parameters in patients with AS. Materials and Methods: This study was designed as a prospective randomized controlled trial. The study was carried out in December 2015 - August 2016. 34 patients who fulfilled the modified New York criteria were enrolled in the study. Patients were randomly assigned into case and control groups each consisting of 17 patients. The cardiac rehabilitation program was applied to the case group for eight weeks. Patient evaluation with clinical assessment, echocardiography, and exercise stress testing was performed before and after treatment. Results: A total of 34 patients made the final study population (37.35± 5.22 years, 55.9% male). There were no significant differences regarding the baseline characteristics between case and control groups. Patients in the case group had better MET levels, exercise time, resting heart rate, and chronotropic reserve than the control patients following cardiac rehabilitation. Conclusion: Our results indicate that significant improvement in cardiac autonomic functions can be obtained in AS patients when the cardiac rehabilitation program is combined with the medical treatment.